Expressions of IFN-γ and IL-4 before and after Treatment of Lupus Nephritis with Traditional Chinese Medicine Combined with Cyclophosphamide and Their Values for Efficacy Prediction and Evaluation - Yan JIANG; Qichang ZHANG; Haoyu WANG; Dabei TANG; Yan ZHANG; Yimo ZHANG; Li YU (Tehran University of Medical Sciences, 2020)
Background: To explore IFN-γ (interferon-γ) and IL-4 (interleukin-4) expressions before and after the treatment of LN (lupus nephritis) and their values for efficacy prediction and evaluation. Methods: Altogether 107 patients with LN treated in the First Hospital of Qiqihaer City, Qiqihar, China from March 2017 to September 2018 were enrolled. Sixty-two patients were treated with cyclophosphamide and prednisolone (control group), while another 45 patients were treated with Qing Shen Fang based on the control group (observation group). Their clinical efficacy and changes in immune indices after treatment were observed. Results: Compared with those in the control group, clinical efficacy, IFN-γ, IL-4, hemoglobin, complements C3 and C4, ESR (erythrocyte sedimentation rate), serum IgG, SLEDAI (Systemic Lupus Erythematosus Disease Activity Index) score, and TCMSSS (Traditional Chinese Medicine Syndrome Score Scale) score were significantly improved after treatment in the study group. Based on the observation, IFN-γ and IL-4 could be used as potential indicators for evaluating clinical efficacy. Conclusion: The combination of cyclophosphamide, prednisolone, and Qing Shen Fang improves conditions of patients with LN and significantly reduces their IFN-γ and IL-4 levels in serum. IFN-γ and IL-4 can be used as potential indicators for the efficacy prediction and evaluation of the disease.